Identification of a Novel C-Terminal Truncated WT1 Isoform with Antagonistic Effects against Major WT1 Isoforms - Tatsumi, Naoya (PLoS One, 2015)
The Wilms’ tumor gene WT1 consists of 10 exons and encodes a zinc finger transcription factor. There are four major WT1 isoforms resulting from alternative splicing at two sites, exon 5 (17AA) and exon 9 (KTS). All major WT1 isoforms are overexpressed in leukemia and solid tumors and play oncogenic roles such as inhibition of apoptosis, and promotion of cell proliferation, migration and invasion. In the present study, a novel alternatively spliced WT1 isoform that had an extended exon 4 (designated as exon 4a) with an additional 153 bp (designated as 4a sequence) at the 3’ end was identified and designated as an Ex4a(+)WT1 isoform. The insertion of exon 4a resulted in the introduction of premature translational stop codons in the reading frame in exon 4a and production of C-terminal truncated WT1 proteins lacking zinc finger DNA-binding domain. Overexpression of the truncated Ex4a(+)WT1 isoform inhibited the major WT1-mediated transcriptional activation of anti-apoptotic Bcl-xL gene promoter and induced mitochondrial damage and apoptosis. Conversely, suppression of the Ex4a(+)WT1 isoform by Ex4a-specific siRNA attenuated apoptosis. These results indicated that the Ex4a(+)WT1 isoform exerted dominant negative effects on anti-apoptotic function of major WT1 isoforms. Ex4a(+)WT1 isoform was endogenously expressed as a minor isoform in myeloid leukemia and solid tumor cells and increased regardless of decrease in major WT1 isoforms during apoptosis, suggesting the dominant negative effects on anti-apoptotic function of major WT1 isoforms. These results indicated that Ex4a(+)WT1 isoform had an important physiological function that regulated oncogenic function of major WT1 isoforms.